PENGARUH FRAUD TRIANGLE TERHADAP DETEKSI KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEKINDONESIA (BEI) - WIDARTI . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
The purpose of this study was to determine the effect Froud detecting fraud triangle in the financial statements. Variables of Fraud Triangle is stability pressuure proxy with ACHANGE, external pressure proxy with FREEC, personal financial need proxy with OSHIP, financial target proxy with the ROA financial , nature of industry proxy with INVENTORY, ineffective monitoring proxy with BDOUT, organizational structure proxy with CEO, and razionaliztion proxy with AUDREPORT. Cheating or Froud diprosikan with earnings management. The sample used in this study as many as 38 companies and data used from 2011 up to 2013. The data anaisis method is linear regression. These results indicate that ACHANGE, ROA and FREEC significantly affect the financial statements fraud or earning management. OSHIP, Inventory, BDOUT, CEO and AUDREPORT not significantly affect the financial statement fraud or earning management.